Gender differences in anti-doping rule violations based on a 19-year data analysis from the Serbian Anti-Doping Agency: national study - Milovanovic, G.; Rasic Ozegovic, J.; Jovicic, D.; Radivojevic, N.; Rancic, N.; Stojicevic, J.; Marjanovic, S.; Vesic, Z.; Vukasinovic-Vesic, M. (Sports, 2025)
Background: Gender differences in anti-doping rule violations (ADRVs) have been noted in international research, yet systematic analyses are rare. This study addresses that gap by providing the first comprehensive evaluation of the doping prevalence by gender in Serbia.